تخريج الفروع على الأصول من خلال مُصَنَّفَيِ الإشارة والمنتقى للإمام الباجي (ت: 474ه) -نماذج من كتاب الأقضية - بكري, مولدي (University of Eloued-جامعة الوادي, 2022)
"ملخّص البحث تخريج الفروع على الأصول من خلال مصنّفي الإشارة والمنتقى للإمام الباجي (ت: 474ه) –نماذج من كتاب الأقضية-؛ أجاب عن إشكال رئيس: ما المقصود بتخريج الفروع على الأصول؟ وما مدى انضباط الإمام الباجي عند بنائه الفروع الفقهيّة من كتابه المنتقى على قواعده الأصوليّة من كتابه الإشارة؛ وذلك من خلال تخريج بعض الفروع الفقهيّة على قواعدها الأصوليّة التي بُنيت عليها، فانتظم الجواب في ثلاثة مباحث؛ أولها: حول الظّروف السّياسيّة والاجتماعيّة والفكريّة التي نشأ فيها الإمام الباجي وحياته العلميّة ووفاته، وثانيها: حول وضع حدّ مناسب لتخريج الفروع على الأصول، وثالثها: في تخريج بعض الفروع الفقهيّة على قواعدها التي بُنيت عليها. وقد أسفر البحث عن عدد من النّتائج؛ أهمها ثلاثة: أوّلها: الأثر الجلي لما أحاط بنشأة الإمام الباجي في شخصيّته العلميّة القويّة. ثانيها: وضع حدّ لتخريج الفروع على الأصول وهو: ""ردّ الفروع الفقهيّة المنصوصة إلى القواعد الأصوليّة التي انبنت عليها، مع بيان وجه الارتباط بينهما"". ثالثها: الانضباط فيما تناولته من نماذج لفروع فقهيّة عند تخريجها على أصولها واضحًا جليًا.""Research Summary Giving off the branches from the origins through the two thesauruses Al ishara( the sign ) and Al montaka (the selected) of Imam al-Baji (D.: 474 Hijri) -samples from the book of Al-akdhia-; it answered a major problematic : What is meant by taking off branches on origins? to what extent is the discipline of Imam al-Baji when constructing the jurisprudential branches from his book al-Muntaqa on its fundamental principles from his book al-Ishara? And that is through giving off some jurisprudential branches from its fundamental principles on which they are based. The answer is organized into three sections; The first: about the political, social and intellectual conditions in which Imam al-Baji grew up, his educational life and his death, and the second: about setting an appropriate limit for the giving off branches from the origins, and third: on the giving off some jurisprudential branches from its bases on which they were built. The research rise a number of results; The most important are three: The first: the clear impact of what surrounded the upbringing of Imam al-Baji in his strong scientific personality. Second: Putting a limit to the giving off of the branches from the origins, which is: “Returning the stipulated jurisprudential branches to the fundamental principles on which they are based, with an explanation of the connection between them”. The third: Discipline regarding the examples of jurisprudential branches that dealt with when giving off them on their origins is clear and obvious.
مذكرة ماستر
Keywords: " الإمام الباجي، المنتقى، الإشارة، فروع، أصول، تخريج. "; Giving, branches, origins, Al ishara, Al montaka, Imam al-Baji